1993
DOI: 10.2527/1993.7182040x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an animal model for across-herd genetic evaluation of number born alive in swine

Abstract: An animal model and computer software were developed to conduct across-herd genetic evaluations using data from producers participating in the Sow Productivity Index program of the American Yorkshire Club. The final data set consisted of 61,596 litter records from 1986 to early 1990. The animal model included fixed contemporary group effects and random additive direct, service sire, permanent environmental, and residual effects. Additive genetic relationships among animals were included. A separate relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…This component is not related to the genotype of the piglet, but accounts for variation of sire permanent effects on sire fertility. The estimated variance components were consistent with reports in previous studies (e.g., See et al, 1993;Woodward et al, 1993;Van der Lende et al, 1999;Hamann et al, 2004). On the other hand, the variance component of sire genetic effects on litter size reflects sire fertility and the contribution to embryo survival through the offspring's genotype.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This component is not related to the genotype of the piglet, but accounts for variation of sire permanent effects on sire fertility. The estimated variance components were consistent with reports in previous studies (e.g., See et al, 1993;Woodward et al, 1993;Van der Lende et al, 1999;Hamann et al, 2004). On the other hand, the variance component of sire genetic effects on litter size reflects sire fertility and the contribution to embryo survival through the offspring's genotype.…”
Section: Discussionsupporting
confidence: 89%
“…Litter size and piglet survival rate are usually treated as traits of the sow. However, the fertilization capacity of the service-sire and the genotype of the piglet could have an effect on these traits (Strang, 1970;Hill and Webb, 1982;See et al, 1993;Woodward et al, 1993;Van der Lende et al, 1999). It therefore seems reasonable to estimate genetic parameters for these traits based on a model that includes effects of sow and service-sire.…”
Section: Introductionmentioning
confidence: 99%
“…They have confirmed the prominent part of sow genotype, but have also shown that both progeny and boa r genotypes significantly influence litter traits. The service sire has a rather limited effect on litter size 0-5% of phenotypic variance) according to Ollivier and Legault 0967), See et al 0993), Beauvois et al 0997), but taking into account this effect has been shown to improve genetic evaluation models for litter size (Woodward et al , 1993;Beauvois, 1996). Similarly, low but non-negligible additive direct genetic effects on embryonic survival ( 4% of phenotypic variance) and litter weight at 21 days (6% of phenotypic variance) were obtained by Gama et al (1991) and Rodriguez et al 0994), respectively.…”
Section: Components Of Genetic Variationmentioning
confidence: 99%
“…When considering the relationship matrix, a joint matrix for sows and boars has generally been defined. In contrast to this most common procedure, Woodward et al (1993) constructed separate relationship matrices for sows and boars.…”
Section: Modelling the Service Sire Effectmentioning
confidence: 99%